Fatal presumed tiger snake (Notechis scutatus) envenomation in a cat with measurement of venom and antivenom concentration. (April 2016) - Padula, Andrew M.; Winkel, Kenneth D.
Abstract: A fatal outcome of a presumed tiger snake ( Notechis scutatus ) envenomation in a cat is described. Detectable venom components and antivenom concentrations in serum from clotted and centrifuged whole blood and urine were measured using a sensitive and specific ELISA. The cat presented in a paralysed state with a markedly elevated serum CK but with normal clotting times. The cat was treated with intravenous fluids and received two vials of equine whole IgG bivalent (tiger and brown snake) antivenom. Despite treatment the cat's condition did not improve and it died 36 h post-presentation. Serum concentration of detectable tiger snake venom components at initial presentation was 311 ng/mL and urine 832 ng/mL, this declined to non-detectable levels in serum 15-min after intravenous antivenom. Urine concentration of detectable tiger snake venom components declined to 22 ng/mL at post-mortem. Measurement of equine anti-tiger snake venom specific antibody demonstrated a concentration of 7.2 Units/mL in serum at post-mortem which had declined from an initial high of 13 Units/mL at 15-min post-antivenom. The ELISA data demonstrated the complete clearance of detectable venom components from serum with no recurrence in the post-mortem samples. Antivenom concentrations in serum at initial presentation were at least 100-fold higher than theoretically required to neutralise the circulating concentrations of venom. Despite the fatal outcome in this case it was concluded that this was unlikely that is was due to insufficient antivenom. Highlights: Clinical case of presumed tiger snake ( Notechis scutatus ) envenoming in a cat. Fatal outcome described ELISA used for serum and urine concentrations of detectable venom components. Antivenom concentration in serum and urine was very elevated at post-mortem. Cat died despite high levels of antivenom present at post-mortem.